Literatura infantil e educação matemática na Educação Infantil: atuações pedagógicas, inspiradas em histórias infantis, com múltiplas linguagens e o voo de crianças bem pequenas - Silva, Maria Kênia Firmino da (2021)
This research deals with the contributions of didactic work with Children's Literature in the mathematical learning of very young children. The general objective of the research was: To analyze the contributions of the didactic use of Children's Literature to the Mathematics Education of very young children. The specific objectives were: 1) To analyze the teaching knowledge of two teachers of very young children about the relationship between Children's Literature and Mathematics Education; 2) To evaluate the implementation of pedagogical performance proposals that relate mathematical content and Children's Literature in a class of very young children aiming at their integral development; ; and 3) To characterize the learning of two very young children's teachers about the relationship between Children's Literature and Mathematics Education. The investigation was carried out in a class of Infantil III, from a public institution of Early Childhood Education in the city of Itaitinga-CE, in which 15 (fifteen) children and 2 (two) regent teachers participated. The qualitative research was carried out in three (3) phases: 1) initial interview with the regent teachers; 2) training with study, selection of children's literature books, planning, implementation and evaluation of pedagogical actions; and 3) final interview with the teachers regentes.The instruments and techniques used were: interview, field diary and study training. In the initial interview, the teachers reported gaps to teach in Early Childhood Education, as well as the fact that they did not learn that children's literature enriches the development and learning of children.During the study training, the teachers deepened on the theme and reported that they understood that it is possible to teach and learn Mathematics with the use of children's stories in Early Childhood Education. The teachers elaborated and implemented three (three) proposals of pedagogical action with the open and closed (Geometry) conceptions, large and small (Quantities and Measures), and much and little (Aritmetics), enabling children to learn Mathematics in various situations: opening and closing a toy, measuring a family person and observing the amount of seeds of a fruit. Due to the pandemic context, the children's productions – drawings and videos – were sent to teachers via WhatsApp.In the final interview, the teachers revealed that the didactic use of Children's Literature in Mathematics Education of very young children is very important, because communication with children is enriched through different languages: musical, pictorial and play.